A meta-analysis and systematic review of the efficacy of enrofloxacin - infections with the bacterium Escherichia coli in pigs - Ščuka, Leon (Slovenian veterinary research, 2004)
A meta-analysis is a method of surveying and combining the results of several independent clinical trials.Besides quantitative integration, a meta-analysis vastly improves the potential for uncovering and studying any differences in available scientific material and provides a basis for plausible explanations of them. It can also lead to new discoveries and allows the aggregation of knowledge in the field of interest. This analytical method is of particular importance when assessing the efficacy of a therapy when the sample sizes of individual studies are too small to cover all aspects of a particular subject or provide a quantitative evaluation of the treatmentćs effect as well as testa null hypothesis. Prior to metaanalysis, the traditional method was a narrative discourse on previous findings, which, however, could be misleading and subjective. Systematic reviews are concise summaries of the best availableevidence that address sharply defined questionsč they seek to assemble and examine all the high quality evidence on any given subject.Enrofloxacin is a fluoroquinolone chemotherapeutic that was developed exclusively for use in veterinary medicine. Shortly after administration, low concentrations have a bactericidal effect against most Gram-negative and Gram-positive bacteria and will also act against mycoplasmata. Twenty-four studies were included in this survey, of which seven were included in a meta-analysis while others were used to build a susceptibility profile of bacteria to enrofloxacin. Eight studies dealt with economic aspects of using enrofloxacin in pig rearing. The total number of animals included in the meta-analysis was 1,296, of which 655 were from the enrofloxacin-treated test groups of the different studies and 641 from their control or alternative treatment groups. In total, there were 19,235 strains of E. coli examined for their susceptibility to enrofloxacin. The results of the meta-analysis are presented graphically. The odds ratio (OR) was used as a measure of the effectsize and the homogeneity andžor heterogeneity values (Q) were calculatedfor the graphs. Additionally, a funnel plot was used to check the dispersion of the studies included in the meta-analysis. The graphs and the calculations (P = 0.43) show that the studies were homogeneous.We also combined the in vitro susceptibility of individual microbes to enrofloxacin and evaluated their MIC values. Each study supported the enrofloxacin treatmentč although there were three results that were statistically significant (P < 0.05), the overall result clearly indicates the high efficacyof enrofloxacin (P < 0.01) in reducing mortality caused by E. coli infections. Of the 19,235 strains surveyed, there were only 3.4 % that were resistant and the MIC values ranged between 0.015 and 0.25 Žgžml. The studies that dealt with the economic aspects of using enrofloxacin to combat E. coli infections, showed that it also has important additional benefits in pig rearing, especially in regards to daily weight gain and feed conversion.Moreover, enrofloxacin reduced the level of haemolytic E. coli excretions and sick animals recovered faster than those in the control or alternative treatment groups did. Our results have confirmed the high efficacyof enrofloxacin usage in E. coli infections, which makes it economically and professionally justifiable for treating coli infections in pigs.
Keywords: bakterijske okužbe; enrofloksancin; prašiči; zdravljenje